Amphiregulin lacks an essential role for the bone anabolic action of parathyroid hormone. (5th December 2015) - Jay, Freya F.; Vaidya, Mithila; Porada, Sabrina M.; Andrukhova, Olena; Schneider, Marlon R.; Erben, Reinhold G.
Abstract: Although parathyroid hormone (PTH) has long been known to act as a bone anabolic agent when administered intermittently, the exact underlying mechanisms remain largely unknown. Amphiregulin (AREG), a ligand of the epidermal growth factor receptor, has been identified to be a PTH target gene in vitro and in vivo . Here, we used female global AREG knockout (AREG-KO) mice to explore the role of AREG in mediating the bone anabolic effects of PTH. AREG-KO mice were characterized by unchanged distal femoral cancellous bone mass and only subtle decreases in bone mineral density (BMD) and cortical thickness at the femoral midshaft at 3 and 8 months of age, relative to wildtype controls. AREG deficiency was associated with complex changes in the mRNA expression of other EGFR ligands in femoral cancellous bone osteoblasts in situ in 3-week-old mice. To examine the bone anabolic effects of PTH in the absence and presence of AREG, we injected 3-month-old AREG-KO females and wildtype control littermates with 80 μg/kg PTH or vehicle 5 times per week over 4 weeks. Intermittent PTH treatment of AREG-KO mice led to increases in femoral trabecular and cortical BMD, cortical thickness, endocortical and periosteal bone formation, cancellous bone formation rate, and serum osteocalcin, comparable to those observed in wildtype control mice. In conclusion, our data indicate that the bone anabolic effects of PTH do not require AREG, at least in 3-month-old female mice. Highlights: Ablation of Amphiregulin (AREG) causes only mild skeletal phenotype in female mice. AREG deficiency causes changes in the expression of other EGFR ligands in osteoblasts. AREG does not have a major role for skeletal integrity in non-growing mice. Intermittent PTH treatment has similar anabolic effects in wild-type and AREG-KO mice. AREG is dispensable for the anabolic actions of intermittent PTH.